Assessing the Factors Militating Against Microfinance in Alleviating Chronic Poverty and Food Insecurity in Rural Northern Ghana - Batinge, Bibiana Koglinuu; Jenkins, Hatice (Springer International Publishing Ag, 2018)
[Abstract Not Available]
3rd International Conference on Banking and Finance Perspectives (ICBFP) -- APR 25-27, 2018 -- Famagusta, CYPRUS
Keywords: Strategy; Women